Why can organizational resilience not be measured? - Sevilla, José; Ruiz-Martín, Cristina; Nebro-Mellado, José Juan; López-Paredes, Adolfo (Vilnius Gediminas Technical University, 2023)
Our aim is to justify why organizational resilience cannot be measured in an ex-ante way and the consequences we can draw from it. To achieve this goal, we examine the relations between different approaches to organizational resilience and the tight interrelation between organizational resilience and organizational and dynamic capabilities. We argue that most proposals about organizational resilience conceptualization, and the metrics derived from them, are closely related. They represent the same core concepts, facts, and relations. Additionally, far from there being no consensus about organizational resilience, researchers are presenting the same ideas with different terms. This implies that there are no better or worse definitions or conceptualizations for organizational resilience, but models are more or less suitable depending on the approach to be established. We agree with the proposal that organizational resilience is a dynamic capability and, as such, it should be studied and considered. This review led us to conclude that because organizational resilience is a dynamic process, it cannot be measured or estimated in an ex-ante way. The fact that organizational resilience cannot be measured brings us to the question of how organizations can address organizational resilience improvement, evaluate their progress, and the tools they can use.
Keywords: Psicología de las organizaciones; Empresas - Gestión; Organizational resilience; Firm behavior; Dynamic capabilities; Management